Abiectum:un estudio de lo abyecto desde la fotografía contemporánea - Velásquez Gaitán, Blanca Diva; Pineda Ramírez, Mauricio; Hernández Rojas, Yesid Fernando (Revista Científica, 2006)
The present investigation project pretends to analyze the artistic work of five contemporary artist work of five contemporary artist in the light of abject concept in photography, appealing to classic considered sources in the history of this discipline, like "about the photography" (1980) of Susan Sontag. Of these ideas, an approach is made to the culture of the image digital expert as a new era, that of the post pothography, marked by the appearence of the digital electronic technology in the recording, manipulation and storage of the images. These images grant a new context to the practice of the picture and the video. Additionally, it is looked for understanding the picture like object and the object like cadaver, according to the theories that describe the abject condition, from those that is presupposed to grant to the picture an unusual thickness, a bottom on which the objective experience supported by the technical, optic and other mechanisms and of the same one will shipwreck.